2002
DOI: 10.1093/jurban/79.4.525
|View full text |Cite
|
Sign up to set email alerts
|

HIV Risk Profile and Prostitution Among Female Street Youths

Abstract: The objective of this study was to compare human immunodeficiency virus (HIV) risk factors among female street youths involved in prostitution and those with no history of prostitution. Youths aged 14 to 25 years were recruited into the Montreal Street Youth Cohort. Semiannually, youths completed an interviewer-administered questionnaire. Statistical analyses comparing characteristics and HIV risk factors for girls involved in prostitution and those never involved were carried out using parametric and nonparam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 45 publications
3
70
1
7
Order By: Relevance
“…Regarding gender, women who inject drugs tend to be younger than their male counterparts, engage in higher rates of needle and syringe sharing, are more likely to share their sex partners' injecting equipment, and engage in riskier sexual practices [53][54][55][56][57][58][59][60]. Regarding the legal environment, ever having been arrested and ever having spent time in prison emerged as risk factors for HIV.…”
Section: Environmental Risk Factors Shaping Hiv Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding gender, women who inject drugs tend to be younger than their male counterparts, engage in higher rates of needle and syringe sharing, are more likely to share their sex partners' injecting equipment, and engage in riskier sexual practices [53][54][55][56][57][58][59][60]. Regarding the legal environment, ever having been arrested and ever having spent time in prison emerged as risk factors for HIV.…”
Section: Environmental Risk Factors Shaping Hiv Riskmentioning
confidence: 99%
“…Despite this issue, the efficacy estimate for NSP seems reasonable because it coincides with the possible HIV-impact of widespread NSP in Tallinn [42] and the impact of high-coverage NSP on other blood-borne infections [56]. It also seems reasonable that ART will have a large impact on parenteral HIV transmission, as evidence shows a huge decrease in plasma viral load when individuals start treatment, and ecological studies have shown associations between PWIDcommunity viral load and HIV incidence at the population level in Vancouver, British Columbia, and Baltimore, Maryland [59]. Due to the uncertainty in the exact effect of ART on HIV transmission in PWID, and because of the low adherence observed among PWID [49], we used a conservative estimate of 80% for the efficacy of ART in reducing HIV transmission risk among PWID.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transactional sex is associated with increased physical and sexual violence, from clients and intimate partners, 9,[16][17][18][19][20][21] as well as higher numbers of sex partners [22][23][24][25] and increased substance use. 22,24,26 Substance use may also contribute to poor decision-making and aggressive behaviors of both victims and perpetrators that increase violence, as well as participation in risky activities to obtain drugs. 7,10 Substance use can also lead to and stem from transactional sex 21 and is associated with multiple partners.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that women identifying as lesbian, bisexual or WSMW have increased odds of binge drinking and drug use. [22][23][24][25] WMSW have been associated with high-risk sex; in two studies at sexually transmitted infection (STI) clinics, WSMW reported more transactional sex compared to heterosexual or WSW women. 28,29 Among drug using women, those who had sex with women had increased transactional sex and numbers of sex partners.…”
Section: Introductionmentioning
confidence: 99%